GOOD SCHOOL GOVERNANCE IMPLEMENTATION THROUGH THE ESTABLISHMENT OF INTERNAL CONTROL UNIT - Maulana Rizky; Sri Setiti; Monry Fraick Nicky (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
This article describes the phenomenon of fraud occurring due to weak internal control system. Based on a study conducted by the Association of Certified Fraud Examiners (ACFE), one of the major causes of fraud is lack of internal control, or 29%, and override of existing internal control, or 20%. (ACFE, 2016). The phenomenon of fraud is still verycommon in Indonesia. Poor organizational governance is also part of the major causes of fraud. Corruption in Indonesia has spread to all sectors, including the education sector. There are many cases of corruption occurring in schools involving principals, treasurers, and teachers. The world of education in Indonesia is severely tarnished by the involvement of teachers in several cases of fraud. If this continues, the world of education will no longer be a role model. Improved organizational governance is necessary for early detection of fraud. This is intended to save Indonesia, especially education sector. The establishment of Internal Control Unit in schools is crucial because the Internal Control Unit serves not only as the implementation of good school governance but also as a tool to prevent fraud at schools.